Assessing the growth and saponin accumulation in hairy and adventitious roots of Vietnamese ginseng (Panax vietnamensis Ha et Grushv.) - Hương, Trịnh Thị; Ngọc, Phạm Bích; Hà, Chu Hoàng; Nhựt, Dương Tấn (Vietnam Journal of Biotechnology, 2016)
In this study, adventitious and hairy roots of Vietnamese ginseng were used to assess the ability of growth and saponin accumulation. Adventitious roots were derived from leaf samples in vitro (1.0 x 1.0 cm of size) cultured on SH medium supplemented with 5.0 mg.l-1 IBA, 30 g.l-1 sucrose, 8 g.l-1 agar, pH 5.8, and subcultured on the same medium for multiplication. Hairy roots were derived from callus infected with Agrobacterium rhizogenes strain ATCC 15834, then these roots were cultured on plant growth regulators-free SH medium supplemented with 50 g.l-1 sucrose, 8 g.l-1 agar, pH 5.8. During the early culture of two months, the results showed that the growth rate of hairy roots was lower than that of adventitious roots. However, in the later period of culture, the growth rate of hairy roots was higher than that of adventitious roots. After 5 months of culture, the growth rate of hairy roots was 20.87 times and they kept growing as well as branching, while the growth rate of adventitious roots was only 13.52 times and they did not grow further after three months of culture. Analytical results showed that the total saponins of total dry matter of hairy roots (0.101 mg) were higher than that of adventitious roots (0.0681 mg). The main ginsenoside of hairy roots (MR2) was also higher than that of adventitious roots 3.03 fold. In addition, the hairy roots grew on plant growth regulators-free medium while adventitious roots grew on medium supplemented with auxin. Therefore, hairy roots proved to be suitable source material for Vietnamese ginseng root biomass production in the bioreactor systems.